New synonyms in the highly diverse caddisfly genus Smicridea (Trichoptera, Hydropsychidae) - Razuri-Gonzales, E (2016)
The authors would like to thank the curators and institutions that loaned the material used in this study: Dr Oliver S. Flint, Jr. (NMNH), Dr Willem Hogenes (NBC), Dr Tobias Malm and Dr Kjell Arne Johanson (NRM), Dr Philip Perkins and Rachel Hawkins (MCZ), and Dave Ruiter (Grants Pass, Oregon, USA). ERG would also like to thank Dr John Luhman for translating the German text in the original description of Smicridea lobata. Dave Ruiter and Dr Brian Armitage provided helpful comments to improve the manuscript. This paper was prepared thanks to a doctoral fellowship from Cienciactiva, initiative from Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica, Peru (contract 277-2015-FONDECYT) awarded to ERG. The research was conducted with the support of Minnesota Agricultural Experiment Station projects MN 17-017 and MN 17-029. This support is gratefully acknowledged.